2019
DOI: 10.1177/1557988319828615
|View full text |Cite|
|
Sign up to set email alerts
|

Behavioral Intention to Initiate Antiretroviral Therapy (ART) Among Chinese HIV-Infected Men Who Have Sex With Men Having High CD4 Count in the Era of “Treatment for All”

Abstract: China has updated its national guideline recommending antiretroviral therapy (ART) to all people living with HIV (PLWH) since 2016. This study was to investigate the prevalence of behavioral intention to initiate ART among HIV-infected men who have sex with men (MSM) with CD4 levels >350 cells/mm3, who had just become eligible to receive free ART in China. A cross-sectional survey was conducted among 262 eligible HIV-infected MSM who had never received ART. The theory of planned behavior (TPB) was used to guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

5
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…In recent published studies, the TPB has been successfully used to explain willingness to use PrEP among GBMSM in general [27], transgender women sex workers [36] and heterosexual population [37]. Moreover, many published studies also used the TPB to explain sexual behaviors [38][39][40], and utilization of HIV testing [41] and antiretroviral therapy [42].…”
Section: Introductionmentioning
confidence: 99%
“…In recent published studies, the TPB has been successfully used to explain willingness to use PrEP among GBMSM in general [27], transgender women sex workers [36] and heterosexual population [37]. Moreover, many published studies also used the TPB to explain sexual behaviors [38][39][40], and utilization of HIV testing [41] and antiretroviral therapy [42].…”
Section: Introductionmentioning
confidence: 99%
“…Another study in South Africa found that among PLWH with CD4 between 201 to 350 cells/ul, those diagnosed after 2011 (South Africa guideline increased the threshold of CD4 to start ART from 200 to 350 cells/ul in 2011) had higher ART initiation rate than those previously diagnosed [19]. Research in China among HIV positive adolescents [20] and MSM [21] showed similar results. These cohort studies mentioned above con rmed the positive effects of broadened spectrum of eligible individuals on improving timely treatment and ART coverage.…”
Section: Introductionmentioning
confidence: 83%
“…Furthermore, PLWH without xed incomes or with relatively low incomes should be prioritized in future programs, as they not only tend to drop out of programs but also to have a higher prevalence of mental health problems one year after receiving ART. Although ART is provided for free to all PLWH in China [53], PLWH still need to pay for compulsory physical examinations every three months. This nancial burden may become a stressor, especially for those with lower incomes.…”
Section: Discussionmentioning
confidence: 99%